Neuroethics 1995–2012. A Bibliometric Analysis of the Guiding Themes of an Emerging Research Field - Leefmann, Jon; Levallois, Clement; Hildt, Elisabeth (Frontiers in Human Neuroscience, 2016)
In bioethics, the first decade of the twenty-first century was characterized by the emergence of interest in the ethical, legal and social aspects of neuroscience research. At the same time an ongoing extension of the topics and phenomena addressed by neuroscientists was observed alongside its rise as one of the leading disciplines in the biomedical science. One of these phenomena addressed by neuroscientists and moral psychologists was the neural processes involved in moral decision-making. Today both strands of research are often addressed under the label of neuroethics. To understand this development we recalled literature from 1995 to 2012 stored in the Mainz Neuroethics Database (i) to investigate the quantitative development of scientific publications in neuroethics; (ii) to explore changes in the topics of neuroethics research within the defined time intervall; (iii) to illustrate the interdependence of different research topics within the neuroethics literature; (iv) to show the development of the distribution of neuroethics research on peer-reviewed journals; and (v) to display the academic background and affiliations of neuroethics researchers. Our analysis exposes that there has been a demonstrative increase of neuroethics research while the issues addressed under this label had mostly been present before the establishment of the field. We show that the research on the ethical, legal and social aspects of neuroscience research is hardly related to neuroscience research on moral decision-making and that the academic backgrounds and affiliations of many neuroethics researchers speak for a very close entanglement of neuroscience and neuroethics. As our article suggests that after more than one decade there still is no dominant agenda for the future of neuroethics research, it calls for more reflection about the theoretical underpinnings and prospects to establish neuroethics as a marked-off research field distinct from neuroscience and the diverse branches of bioethics.